Collaborative Ontology Development for the Geosciences. Issue 6 (11th November 2013) - Kalbasi, Reza; Janowicz, Krzysztof; Reitsma, Femke; Boerboom, Luc; Alesheikh, Ali
Abstract Ontology‐based information publishing, retrieval, reuse, and integration have become popular research topics to address the challenges involved in exchanging data between heterogeneous sources. However, in most cases ontologies are still developed in a centralized top‐down manner by a few knowledge engineers. Consequently, the role that developers play in conceptualizing a domain such as the geosciences is disproportional compared with the role of domain experts and especially potential end‐users. These and other drawbacks have stimulated the creation of new methodologies focusing around collaboration. Based on a review of existing approaches, this article presents a two‐step methodology and implementation to foster collaborative ontology engineering in the geosciences. Our approach consists of the development of a minimalistic core ontology acting as a catalyst and the creation of a virtual collaborative development cycle. Both methodology and prototypical implementation have been tested in the context of the EU‐funded ForeStClim project which addresses environmental protection with respect to forests and climate change.